The proteomic response of larvae of the Sydney rock oyster, saccostrea glomerata to elevated pCO 2 - Parker, L M; Ross, P M; Raftos, D; Thompson, E T; O'Connor, W A (Australian Zoologist, 2011)
The acidification of oceans is predicted to fundamentally alter marine ecosystems. Previous studies have found that elevated CO 2 has an effect on adult calcification, fertilisation and larval development, perhaps because of the organisms' inability to regulate acid-base status, but little is known about the mechanisms that underlie such responses. This study investigated the growth response of larvae of a wild and selectively bred line of the Sydney rock oyster, Saccostrea glomerata, to elevated CO 2 and measured the pattern of expression of proteins. Overall exposure to elevated CO 2 caused a significant reduction in the shell length of D-veliger larvae of the wild, but not in the selectively bred line. Prior to this study, differences in growth between selectively bred and wild oysters have only been found following settlement Proteome analysis of D-veliger larvae using two-dimensional gel electrophoresis detected a significantly greater number of protein spots in selectively bred compared to wild oyster lines. In addition, a comparison of the proteins expressed between selectively bred and wild larvae exposed to elevated CO 2 and ambient conditions showed that a number of proteins were up- or down-regulated and in some cases, switched on at elevated CO 2 in selectively bred lines, but not found in the wild lines. Identification of these differentially expressed proteins may assist to "climate proof" of important aquacultural industries.